EKSPRESI PROGESTERONE RECEPTOR (PR) PADA BENIGN, ATYPICAL DAN ANAPLASTIC MENINGIOMA - Poniman, Jeni (Alami Journal (Alauddin Islamic Medical) Journal, 2020)
ABSTRAK Background: Meningioma is the most common brain tumour in adult which treatment and follow-up depend on the histologic grade. Aim: This research aim is to assess the difference of Progesterone Receptor (PR) expression in 3 grade groups meningioma which are benign, atypical and anaplastic meningioma. Method: It is an analytic observational research with cross sectional design using immunohistochemical staining of PR antibody on 30 samples of paraffin blocks. Result: PR immunostaining positive in benign and atypical meningioma, and PR immunostaining negative in anaplastic meningioma with p value less than 0.05 (p = 0.000). Conclusion: There is difference of PR expression in each meningioma grade groups; benign, atypical and anaplastic meningioma. Key Words: progesterone receptor, meningioma